The Political Use of Epicureanism in Filelfo’s Commentationes Florentinae de exilio - Vilar, Mariano (Renaissance and Reformation / Renaissance et Réforme, 2019)
Francesco Filelfo’s Commentationes Florentinae de exilio (ca. 1440) presents us with a dialogue among a group of nobles and scholars who debate several issues in moral philosophy to console themselves on their defeat by Cosimo de’ Medici. The role of pleasure in human happiness is treated in several sections of the work in relation to three of Filelfo’s main goals: the condemnation of his rivals Poggio Bracciolini and Niccolò Niccoli (both of whom were connected with the Medicean circle), the exaltation of his own philological erudition, and the attack on Cosimo’s regime. There is textual evidence that Filelfo used some of the ideas presented by Valla in his De voluptate (1431) for the purpose of satirizing his rivals and showing that their interest in Epicureanism was morally and intellectually flawed.